Towards More Effective Social Assistance in Russia An Update of the System Performance Considering New National Target of Halving Poverty by 2024 - Yemtsov, Ruslan (World Bank E-Library Archive, 2019)
This update is intended to feed into this on-going process, enabling the World Bank team to continue to support the Government of the Russian Federation in its efforts to improve efficacy of its social assistance system. Through the RAS project, the social assistance team of the World Bank has established itself as credible source of robust analysis and solid technical advice